Cenários de mudanças climáticas para a América do Sul : impacto no zoneamento agroclimático da cana-de-açúcar - Castro, Fábio da Silveira (2014)
The Intergovernmental Panel on Climate Change (IPCC) through its Fourth Assessment Report of Global Climate Change (IPCC-AR4), published in 2007, assign emissions of greenhouse gases as the main cause of the increase in average temperatures and alert an i